Sirolimus treatment for tuberous sclerosis complex prior to epilepsy: Evidence from a registry-based real-world study. (April 2022) - Shen, Yan-Wen; Wang, Yang-Yang; Zhang, Meng-Na; Xu, Yong; Lu, Qian; He, Wen; Chen, Hui-Min; Liu, Li-Ying; Pang, Ling-Yu; Wang, Qiu-Hong; Dun, Shuo; Li, Yu-Fen; et al.
Highlights: Sirolimus can be safely introduced to TSC neonates and young infants under frequent drug concentration monitor. Early use of sirolimus can modify the natural process of seizure in TSC by delaying the onset of all seizures subtypes and reducing the severity. Early use of sirolimus can significantly reduce the risk for new-onset infantile spasms and change the natural composition of seizures. The anti-epileptogenic effect of sirolimus might be mild and time-dependent, and possibly dose-dependent as well. Abnormal EEG might not be a must for early sirolimus intervention. Abstract: Objective: To evaluate whether sirolimus treatment could relieve the later burden of new-onset seizures in patients with tuberous sclerosis complex (TSC) prior to epilepsy. Methods: A real-world matched case-control study was nested in another registry cohort study. Infants with TSC (<12 months old) without seizures whose parents agreed on sirolimus treatment for other symptoms were eligible for inclusion to the early sirolimus (ES) group. These patients were enrolled from 2015 to 2018. Controls in the late sirolimus (LS) group were matched from the registry cohort database for 2015–2018. Age and genotype were used as the initial stratifying criteria and other symptoms as the greedy matching criteria at a matching ratio of 1:4. None of the preventive drugs were introduced before seizure onset or before 2 years of age in the LS group. Both groups were followed up until June 2020. The primary objective was a comparison of the characteristics of the first seizure between the two groups. The secondary objective was the assessment of the final seizure status at the endpoint. Results: There were 42 and 168 patients with TSC in the ES and LS groups, respectively. Early sirolimus treatment significantly reduced the seizure onset, especially in the patients aged <6 months. The mean onset-age was significantly delayed by sirolimus treatment (11.34±7.93 months vs. 6.94±6.03 months, P <0.001). The subtype of seizures that benefited the most was spastic (onset) seizures (all were infantile spasms) [5/42 (11.90%) vs. 73/168 (43.45%), P <0.001]; these seizures were either eliminated or alleviated. The sirolimus treatment addition prior to seizures was more effective than its addition after seizures in reducing drug-resistant epilepsy [10/42 (23.81%) vs. 70/147 (47.62%), P =0.004]. Conclusion: Early sirolimus treatment for TSC effectively modified the disease by preventing infantile spasms, delaying seizure onset, and relieving its severity. The anti-epileptogenic effect of sirolimus may be time- and dose-dependent.